Uptown night market, tourists’ satisfaction and behaviour intention / Nhajhazlynda Kamaruddin - Kamaruddin, Nhajhazlynda (2013)
Uptown night markets are definitely popular destinations among local communities and domestic tourists as it gave an insight into traditional Malaysia way of life. Night markets have been long enough existed and it blends into the Malaysian community activity that offers variety of product offer, convenient to access and offering affordable price to the visitors. Besides, night market also reflected a piece of Malaysian unique culture as it portrayed the eating preference, interaction pattern and some of evening leisure activities of the various ethnic group in the country. The cultural uniqueness of night market exposes night market to be must-visit destination for both local communities as well as tourists. Through understanding of the attributes of night market, tourist’s satisfaction of night market is important element in developing a night market as a popular tourist destination. The purpose of this study is to investigate the tourist’s satisfaction and their behavioural intention toward Uptown night market. The research methodology was adopted a descriptive research design using a quantitative approach. The samples for this study are the domestic tourists who were attended and experienced the Uptown night market. This study area covers two Uptown night market in Selangor which is located at Uptown Night Market Shah Alam and Kota Damansara. To the end, this study be able to contribute to a deeper understanding about the tourist’s satisfaction of Uptown Night Market attributes and their behavioural intention as well as in term of development opportunities and constrains of Uptown night market to be promoted as one of tourism destination attraction in Malaysia.